Induced dipole moments in amorphous ZnCdS catalysts facilitate photocatalytic H2 evolution - Xin Wang; Boyan Liu; Siqing Ma; Yingjuan Zhang; Lianzhou Wang; Gangqiang Zhu; Wei Huang; Songcan Wang (Nature Communications, 2024)
Abstract Amorphous semiconductors without perfect crystalline lattice structures are usually considered to be unfavorable for photocatalysis due to the presence of enriched trap states and defects. Here we demonstrate that breaking long-range atomic order in an amorphous ZnCdS photocatalyst can induce dipole moments and generate strong electric fields within the particles which facilitates charge separation and transfer. Loading 1 wt.% of low-cost Co-MoSx cocatalysts to the ZnCdS material increases the H2 evolution rate to 70.13 mmol g−1 h−1, which is over 5 times higher than its crystalline counterpart and is stable over the long-term up to 160 h. A flexible 20 cm × 20 cm Co-MoSx/ZnCdS film is prepared by a facile blade-coating technique and can generate numerous observable H2 bubbles under natural sunlight, exhibiting potential for scale-up solar H2 production.